Fragile eternity - Marr, Melissa (New York : HarperCollins Childrens Books, 2010)
Aislinn and Seth struggle with the unforeseen consequences of Aislinn's transformation from mortal girl to faery queen as the world teeters on the brink of cataclysmic violence.
"A Wicked lovely book"--Cover.
"New short story inside"--Cover.
Includes "Stopping time" a never-before published short story in the world of Wicked lovely.
Sequel to: Wicked lovely and Ink exchange.
HL 650
Accelerated Reader AR
Keywords: Fairies -- Juvenile fiction; Queens -- Juvenile fiction; Teenage girls -- Juvenile fiction; Young adult fiction; Fantasy fiction